2019
DOI: 10.1002/jms.4360
|View full text |Cite|
|
Sign up to set email alerts
|

Gas‐phase functionalized carbon‐carbon coupling reactions catalyzed by Ni (II) complexes

Abstract: Gas‐phase C―C coupling reactions mediated by Ni (II) complexes were studied using a linear quadrupole ion trap mass spectrometer. Ternary nickel cationic carboxylate complexes, [(phen)Ni (OOCR1)]+ (where phen = 1,10‐phenanthroline), were formed by electrospray ionization. Upon collision‐induced dissociation (CID), they extrude CO2 forming the organometallic cation [(phen)Ni(R1)]+, which undergoes gas‐phase ion‐molecule reactions (IMR) with acetate esters CH3COOR2 to yield the acetate complex [(phen)Ni (OOCCH3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This is explained by the additional stabilization of Pd-hexyl complex 3-Pd by Pd−H agostic interactions. We have reported similar interactions in the gas phase found in Ni-organic complexes 18 and in Pd and Ni complexes with alkyl chains with two carbons or longer. 9,10 These types of interactions have also been found in solution and in the solid phase for Ni, Pd, and Pt complexes.…”
Section: Introductionsupporting
confidence: 66%
“…This is explained by the additional stabilization of Pd-hexyl complex 3-Pd by Pd−H agostic interactions. We have reported similar interactions in the gas phase found in Ni-organic complexes 18 and in Pd and Ni complexes with alkyl chains with two carbons or longer. 9,10 These types of interactions have also been found in solution and in the solid phase for Ni, Pd, and Pt complexes.…”
Section: Introductionsupporting
confidence: 66%
“…Most of the previous gas‐phase decarboxylation reactions [Eq. (4)] were limited to simple coordinated anions such as formate, acetate, and benzoate [31,32] which undergo decarboxylation upon CID. Decarboxylation accompanied by dehydrogenation, as seen with the fatty acids above, can only be observed for carboxylic acids with α and β hydrogen atoms in the side chain.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting conformer of 1‐Pd is then stabilized via agostic interactions between Pd and β‐H atom of the side chain. Such interactions are quite well known, [31,38] and their importance in subsequent fragmentation reactions will be addressed below. The next barrier, lower in energy than the critical one by 6.4 kJ/mol, corresponds to the extrusion of CO 2 via a four‐membered TS, leading to the formation of organopalladium species 2‐Pd .…”
Section: Resultsmentioning
confidence: 99%
“…Another C–C coupling system published by Piacentino et al demonstrated the ability of Pesci decarboxylation products (O'Hair & Rijs, 2015) to react with a wide range of esters to form new C–C bonds as shown in Equations () and () below. (Piacentino et al, 2019) false[false(phenfalse)Mfalse(normalO2CRfalse)false]+false[false(phenfalse)Mfalse(normalRfalse)false]++CO2, ${[(\text{phen}){\rm{M}}({{\rm{O}}}_{2}\text{CR})]}^{+}\to {[(\text{phen}){\rm{M}}({\rm{R}})]}^{+}+{\text{CO}}_{2},$ [(phen)normalM(R)]++normalRfalse′normalO2CR''[(phen)normalM(normalO2CR)]++normalRnormalRfalse′, ${[(\text{phen}){\rm{M}}({\rm{R}})]}^{+}+{{\rm{R}}^{\prime} {\rm{O}}}_{2}\text{CR''}\to {[(\text{phen}){\rm{M}}({{\rm{O}}}_{2}\text{CR}^{\prime\prime} )]}^{+}+{\rm{R}} \mbox{-} {\rm{R}}^{\prime} ,$ *catalytic.5emif.5emR=R. $* catalytic\,if\,R\mbox{''}=R.$…”
Section: Metal Ion Catalysis Chemistrymentioning
confidence: 98%